Caribbean Youth Development : Issues and Policy Directions - World Bank (Washington, DC, 2013)
This report examines youth development in the Caribbean today. The objectives of the report are threefold, it aims to 1) identify the risk and protective factor and determinats of youth behaviors and development, 2) demonstrate that the negative behaviors of youth are costly, not only to the youth themselves but to society as a whole, and 3) identifies key intervention points for youth development, taking into account identified risk and protective factors for the Caribbean. For the purpose of the study, youth is defined as spanning the adolescent period from 10 to 24 years of age. Youth or adolescent development thus refers to the physical, social, and emotional processes of maturation from childhood to adulthood, with biological processes riving the initiation of adolescence and social factors largely determining the initiation of adulthood. The study uses an "ecological" framework to demonstrate the linkages between a) the under-lying risk and protective factors of youth behaviors, b) youth outcomes, and c) subsequent adult outcomes. It is termed "ecological" because the framework shows the relationship between the individual adolescent and his or her environment. Risk factors are those factors that increase the likelihood of experiencing negative outcomes. Protective factors counterbalance the risk factors.